Ombudsman (Muhtasib) in business regulation: A cross cultural analysis - Omoola Olelakan, Sodiq; Mohamed, Nurah Sabahiah (University of Management and Technology, Lahore, Pakistan, 2017)
Ombudsman, known as Muhtasib in Islamic tradition: is an independant, impartial, and confidential complaint handler who serves as an alternative means of dispute resolution. Historical account shows that ombudsman institutions have been known in different cultures with various nomenclatures. The Islamic Muhtasib which has been proven to predate its similitude in other cultures is an evidence of cross-cultural learning from Islamic tradition to other cultures. This remains factual notwithstanding the lack of homogeneity of its origin as well as its modern usage in public administration, human right and business regulation. Through the use of doctrinal approach and library tools, the paper presents histology of ombudsman in the Islamic, Greek, Chinese and Scandinavian tradition. The study finds that ombudsman in the Islamic legal tradition is more suitable to business regulation than similar institution which exists in other cultures